Developing Biofuel Bioprocesses Using Systems and Synthetic Biology - Clay, Sylvia M.; Fong, Stephen S. (SpringerBriefs in Systems Biology, 2013)
Advances in technological and analytical methods have fostered rapid growth of systems biology and synthetic biology.  There continues to be rapid changes and discoveries in both fields with a small number of recent peer-reviewed reviews indicating some of the relationships between systems biology and synthetic biology.  This proposed SpringerBrief will cover core concepts of systems biology and synthetic biology and illustrate the implementation of associated research methodologies for an integrated approach to specifically address engineering microorganisms for biofuel production.